Industrial Associations as a Channel of Business-Government Interactions in an Imperfect Institutional Environment: The Russian Case - Andrei Yakovlev; Andrei Govorun (Leibniz-Institut für Wirtschaftsforschung Halle (IWH), 2011)
International lessons from emerging economies suggest that business associations may provide an effective channel of communication between the government and the private sector. This function of business associations may become still more important in transition economies, where old mechanisms for coordinating enterprise activities have been destroyed, while the new ones have not been established yet. In this context, Russian experience is a matter of interest, because for a long time, Russia was regarded as a striking example of state failures and market failures. Consequently, the key point of our study was a description of the role and place of business associations in the presentday Russian economy and their interaction with member companies and bodies of state administration. Relying on the survey data of 957 manufacturing firms conducted in 2009, we found that business associations are more frequently joined by larger companies, firms located in regional capital cities, and firms active in investment and innovation. By contrast, business associations tend to be less frequently joined by business groups' subsidiaries and firms that were non-responsive about their respective ownership structures. Our regression analysis has also confirmed that business associations are a component of what Frye (2002) calls an 'elite exchange'- although only on regional and local levels. These 'exchanges' imply that members of business associations, on the one hand, more actively assist regional and local authorities in social development of their regions, and on the other hand more often receive support from authorities. However, this effect is insignificant in terms of support from the federal government. In general, our results allow us to believe that at present, business associations (especially the industry-wide and 'leading' ones) consolidate the most active, advanced companies and act as collective representatives of their interests. For this reason, business associations can be regarded as interface units between the authorities and businesses and as a possible instrument for promotion of economic development. – – Internationale Studien legen nahe, dass Wirtschaftsverbände in Entwicklungsökonomien als Schnittstelle in der Kommunikation zwischen Staat und privatem Sektor dienen können. Da Russland lange Zeit als treffendes Beispiel für Staats- und Marktversagen galt, liegt der Schwerpunkt dieser Studie auf einer Analyse der gegenwärtigen Rolle der russischen Wirtschaftsverbände und deren Interaktion mit Mitgliedsunternehmen und staatlichen Institutionen. Nach Auswertung von Befragungsdaten, die 2009 in 957 Industrieunternehmen erhoben wurden, zeigt sich, dass große Unternehmen, Unternehmen mit Niederlassungen in regionalen Ballungszentren und Unternehmen, die Investitionen und Innovationen tätigen, häufiger in Wirtschaftsverbänden vertreten sind als Tochtergesellschaften von Großkonzernen und Unternehmen, die sich zu ihren Eigentumsverhältnissen nicht äußern wollten. Die Regressionsanalyse zeigt auch, dass Wirtschaftsverbände Teil dessen sind, was Frye (2002) 'elite exchange' nennt - wenngleich dieser Austausch nur auf regionaler und lokaler Ebene stattfindet. Diese 'exchanges' beinhalten, dass die Mitglieder der Wirtschaftsverbände auf der einen Seite aktiver die regionalen und lokalen Institutionen unterstützen und auf der anderen Seite auch häufiger Unterstützung von diesen Institutionen erhalten. Dieser Effekt ist jedoch insignifikant für die gesamtstaatliche Ebene. Die Ergebnisse deuten darauf hin, dass Wirtschaftsverbände als Schnittstelle zwischen staatlichen Institutionen und Wirtschaft und somit als mögliches Instrument zur Förderung der wirtschaftlichen Entwicklung beitragen können.
urn:nbn:de:101:1-201112215414
Keywords: L31; O17; 330; business associations; economic growth; state-business relations; collective actions; Wirtschaftsverbände; Wirtschaftswachstum; Staat-Wirtschaft-Beziehungen; Verbandsaktivitäten